2009
DOI: 10.1051/alr/2009038
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging as a means to assess the body growth and the gonad development of the oysterCrassostrea gigas

Abstract: -To make a preliminary exploration of the possibilities and limits of magnetic resonance imaging (MRI) for assessing body growth and gonad development of the Pacific oyster, Crassostrea gigas, individual monitoring was conducted on diploid and triploid oysters in their second year, maintained from February to October in a pond on the French Atlantic coast. Magnetic resonance imaging was done on each oyster on five dates during the study period. From these images, variations in the volumes of the flesh, digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The pixels within this polygon were considered as belonging to the gonad, and their number was multiplied by the unit surface of the pixel. Preliminary trials, done using the same method in previous years (Davenel et al, 2006, Hatt et al, 2009, concluded that the grey-level for mature gonads on MRI was between 166 and 510. On the grey-level histograms established on whole oyster body soft tissues with the methods described in subsection 2.2, all the voxels above 165 were counted as a part of the mature gonads.…”
Section: Analysis Of Mri Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pixels within this polygon were considered as belonging to the gonad, and their number was multiplied by the unit surface of the pixel. Preliminary trials, done using the same method in previous years (Davenel et al, 2006, Hatt et al, 2009, concluded that the grey-level for mature gonads on MRI was between 166 and 510. On the grey-level histograms established on whole oyster body soft tissues with the methods described in subsection 2.2, all the voxels above 165 were counted as a part of the mature gonads.…”
Section: Analysis Of Mri Imagesmentioning
confidence: 99%
“…Considering the large investment oysters make in reproduction (Bourles et al, 2009, Deslous-Paoli and Héral, 1988, Pouvreau et al, 2006b) and the observation of selected oyster lines with different gonad average sizes and different susceptibilities to summer mortality (Samain et al, 2007, Huvet et al, 2010, the gonad was considered a priority organ for study. Further research using the MRI method highlighted a positive relationship between the effort devoted to reproduction and subsequent growth of the tissues and showed that growth variability within a group of oysters was overestimated by the more commonly used histological method (Hatt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on MRI reported that this technique was able to quantify the volume and mass of the whole flesh and of some organs in the cupped oyster [20][21][22] and in the flat oyster [23]. However, there are too few studies comparing different non-destructive techniques to determine the damage caused by the Polydora worm.…”
Section: Introductionmentioning
confidence: 99%